Transcriptoma da glândula de peçonha de Crotalus durissus collilineatus: análise do perfil de expressão gênica - França, Johara Boldrini (2008)
Crotalus durissus rattlesnakes are responsible for the major cases of lethality involving snakebites in Brazil. Crotalus d. collilineatus subspecie is related to a great number of accidents in Southeast and Central west regions, but few studies on its venom composition have been carried out. As an attempt to describe the transcriptional profile of the C. d. colllineatus venom gland, we generated a cDNA library and sequences obtained of random selected clones could be identified by similarity searches on existing databases. A total of 489 out of 673 ESTs produced readable sequences comprising 201 singletons and 47 clusters of two or more ESTs. From 248 contiguous sequences, 150 (60.5%) produced significant hits to known sequences. The results showed a predominance of toxin-coding expressed sequence tags (ESTs) instead of transcripts coding for proteins involved in all cellular functions. The most frequent toxin for this library was crotoxin, comprising 88% of toxin-coding sequences. The crotoxin B, a basic phospholipase A2 (PLA2) subunit of crotoxin, was represented in more variable forms comparing to the nonenzymatic subunit (crotoxin A), and the most of sequences coding this molecule were identified as CB1 isoform from Crotalus durissus terrificus venom. 4% of toxin-related sequences in this study were identified as Growth Factors, comprising five sequences for vascular endothelial growth factor (VEGF) and one for nerve growth factor (NGF) that showed 100% of identity with C. d. terrificus NGF. We also identified two clusters for metalloprotease from PII class comprising 3% of toxins, and two for serine proteases, including gyroxin (2.5%). The remaining 2.5% of toxin-coding ESTs represent singletons identified as homologue sequences to cardiotoxin, convulxin, angiotensin converting enzyme inhibitor and C-type natriuretic peptide, Ohanin, crotamin and PLA2 inhibitor. These results allowed the identifications of the most common classes of snake venom toxins, however some of them were unknown for C. durissus collilinatus subspecie, and even for Crotalus durissus specie, such as cardiotoxins and VEGF.